2020
DOI: 10.31538/nzh.v3i2.594
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Moderation Through Education Characters of Aswaja An-Nahdliyyah

Abstract: This study aims to elaborate the strengthening of Islamic moderateism through Aswaja An-Nahdliyyah character education. The researcher describes the behavior of Aswaja An-Nahdliyyah character education practiced by Islamic educational institutions as a basis for strengthening religious moderatism. The role of Islamic education institutions in applying moderate Islamic understanding in this disruption era is necessary. Because, students are faced with conditions of changing the order of values ​​and traditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
0
11
0
6
Order By: Relevance
“…Seperti hasil penelitian (Ahmad et al, 2019) bahwa seorang merasa benar dengan dirinya sehingga menutup diri dan merasa suci (structure of pureness). Menerapakan pembelajaran Islam moderat di perguruan tinggi juga bisa dibilang terlambat dikarenakan seorang seharusnya dibekali setiap pendidikan Islam moderat baik dalam sekolah atau dalam kehidupan sehari-hari (Saefudin and Fatihah, 2020). Disamping Perguruan Tinggi dan sekolah, Pesantren juga termasuk yang menerapkan nilai Islam moderat (Ahdar et al, 2020;Ni'am, 2015).…”
Section: Hasil Dan Pembahasanunclassified
“…Seperti hasil penelitian (Ahmad et al, 2019) bahwa seorang merasa benar dengan dirinya sehingga menutup diri dan merasa suci (structure of pureness). Menerapakan pembelajaran Islam moderat di perguruan tinggi juga bisa dibilang terlambat dikarenakan seorang seharusnya dibekali setiap pendidikan Islam moderat baik dalam sekolah atau dalam kehidupan sehari-hari (Saefudin and Fatihah, 2020). Disamping Perguruan Tinggi dan sekolah, Pesantren juga termasuk yang menerapkan nilai Islam moderat (Ahdar et al, 2020;Ni'am, 2015).…”
Section: Hasil Dan Pembahasanunclassified
“…One of the belief that highlights the attitude of moderation in Indonesia is the Aswaja an-Nahdliyah. Various researches has revealed that the education of Aswaja an-Nahdliyah has the real contribution to the attempt to prevent radicalism of religion (Rifa'i et al, 2017;Saefudin & Fatihah, 2020;Syarif, 2021). The material of Aswaja with the moderate values (tawassuth) that keeps on being taught to the students is seen to give them a more comprehensive understanding about religion that can compromise two extreme believes, the extreme right (radical) and extreme left (liberal) (Labiba, 2021;Wahyudin, 2017).…”
Section: ‫بسلطة‬ ‫اف‬ ‫االعرت‬ ‫الفقهية،‬ ‫املدرسة‬mentioning
confidence: 99%
“…Fenomena belajar agama di media sosial juga menjadi sorotan akhir-akhir ini (Faisal, 2020;Fakhruroji et al, 2020;Saputra, 2017;Latifah & Romario, 2019;Nugraha, 2013;Nugraha, 2015). Munculnya akun-akun dakwah di instagram menunjukkan fenomena perkembangan strategi dakwah semakin pesat dengan memanfaatkan teknologi sebagai media informasi global (Saefudin & Al Fatihah, 2020).…”
Section: Pendahuluanunclassified